Ida Rubinstein : revolutionary dancer, actress, and impresario - Chazin-Bennahum, Judith (State University of New York Press, 2022)
The critical biography of a dynamic and under-represented figure who produced and starred in some of the most innovative works of her day.
Keywords: Rubinstein, Ida, -- 1883-1960.; Women dancers -- France -- Paris -- Biography.; Choreographers -- France -- Paris -- Biography.; Women dancers -- Russia (Federation) -- Biography.; Danseuses -- France -- Paris -- Biographies.; Chorégraphes -- France -- Paris -- Biographies.; Danseuses -- Russie -- Biographies.; Choreographers.; Women dancers.; France -- Paris.; Russia (Federation); Biographies.